Benchmark for Nonlinear Consolidation of a Soil Deposit by Considering Depth-Dependent Initial Effective Pressure - Lu Wang (Advances in Civil Engineering)
Analytical solutions for 1D nonlinear consolidation of soils are widely applied to calculate consolidation settlement for their simplicity and convenience. Furthermore, analytical solutions can provide valid benchmark for numerical solutions of nonlinear consolidation. However, the existing analytical solutions for 1D nonlinear consolidation assume the initial effective stress to remain constant in the whole deposit. In practice, the initial effective stress increases with depth in a soil deposit. The existing analytical solutions for 1D nonlinear consolidation are lack of consideration about the variation of initial effective stress along with depth, so there is no benchmark for evaluating the corresponding numerical calculation. In this study, an analytical solution for nonlinear consolidation is developed under a special case, considering the linear increase of initial effective stress with the depth, which provides a benchmark for the corresponding numerical calculation of nonlinear consolidation. To facilitate the verification of the reliability of the numerical calculations of nonlinear consolidation, the pore pressure dissipation curves and settlement curves with time for conditions of PTIB (the case for a permeable top surface and an impermeable bottom surface is referred to as PTIB) and PTPB (the case for a permeable top surface and a permeable bottom surface is named as PTPB) are provided in this paper, thus providing some validation data for future calculations of nonlinear consolidation considering a linear increase in the initial effective stress with depth.